System Quality Dominance in MSME Accounting Technology Adoption and Operational Efficiency - Iwan Setya Putra; Tanto Askriyandoko Putro; Hanif Yusuf Seputro (Universitas Trunojoyo Madura, 2026)
The adoption of accounting software by micro, small, and medium-sized enterprises (MSMEs) does not automatically guarantee improved operational outcomes. This study empirically examines how perceived usefulness, perceived ease of use, and system quality influence operational efficiency through the mediating role of user satisfaction. Integrating the Technology Acceptance Model (TAM) with the DeLone and McLean Information Systems (DM IS) Success Model, we test seven hypotheses using structural equation modeling (SEM) on survey data from 212 Indonesian MSME accounting software users. Results indicate that system quality and perceived usefulness significantly enhance user satisfaction, while perceived ease of use shows no significant effect. User satisfaction fully mediates the relationship between system quality and operational efficiency, whereas the direct effect of system quality on operational efficiency is non-significant. These findings suggest that robust system quality supersedes interface simplicity as the primary driver of satisfaction and efficiency in resource-constrained MSME settings. Software developers should prioritize backend robustness and functional completeness, while MSME managers should evaluate accounting software based on system reliability rather than ease of initial use.